Transmission electron microscopic characterization of granulocytes of pig (Sus scrofa)* - MEHTA, SURESH; SINGH, ISHWAR; MRIGESH, MEENA (The Indian Journal of Animal Sciences, 2012)
Transmission electron microscopic characterizations of granulocytes of pig were carried out on ten apparently healthy adult pigs. Ultrastructurally the neutrophils were roughly round in shape with number of small cytoplasmic processes. Cytoplasmic granules of the neutrophils varied greatly in shape, size and density. Populations of electron lucent granules were comparatively greater than electron dense. Eosinophils were round in outline and the cytoplasm had four types of cytoplasmic granules. The basophils were roughly spherical in outline with cytoplasmic granules. One type of granules was less electron dense and very small in size whereas second type of granules were highly electron dense and showed pleomorphism.